Variations of the physical parameters of the blazar Mrk 421 based on analysis of the spectral energy distributions. (21st May 2020) - Yamada, Yurika; Uemura, Makoto; Itoh, Ryosuke; Fukazawa, Yasushi; Ohno, Masanori; Imazato, Fumiya
Abstract: We report on the variations of the physical parameters of the jet observed in the blazar Mrk 421, and discuss the origin of X-ray flares in the jet, based on analysis of several spectral energy distributions (SEDs). The SEDs are modeled using the one-zone synchrotron self-Compton model, its parameters determined using a Markov chain Monte Carlo method. The lack of data at TeV energies means many of the parameters cannot be uniquely determined and are correlated. These are studied in detail. We find that the optimal solution can be uniquely determined only when we apply a constraint to one of four parameters: the magnetic field ( B ), the Doppler factor, the size of the emitting region, and the normalization factor of the electron energy distribution. We used 31 sets of SEDs from 2009 to 2014 with optical–UV data observed with UVOT/Swift and the Kanata telescope, X-ray data with XRT/Swift, and γ-ray data with the Fermi Large Area Telescope. The result of our SED analysis suggests that, in the X-ray faint state, the emission occurs in a relatively small area (∼10 16  cm) with a relatively strong magnetic field ( B ∼ 10 −1  G). The X-ray bright state shows a tendency opposite to that of the faint state, that is, a large emitting area (∼10 18  cm), probably downstream of the jet, and a weak magnetic field ( B ∼ 10 −3  G). The high X-ray flux was due to an increase in the maximum energy of electrons. On the other hand, the presence of two kinds of emitting areas implies that the one-zone model is unsuitable for reproducing at least part of the observed SEDs.